Effect of Turmeric Flour (Curcuma domestica) and Fish Oil on Daily Egg Production and Organoleptics of Quail Eggs (Coturnix-coturnix japonica) - Lovela, Aprinda Ratna; Al-Arief, Moh. Anam; Ismudiono, Ismudiono; Supranianondo, Kusnoto; Lokapirnasari, Widya Paramita; Sabdoningrum, Emy Koestanti (Journal of Basic Medical Veterinary, 2021)
The purpose of this study was to determine the effect of adding the concentration of turmeric flour and fish oil to the quail formula feed. This research is an experimental study using the factorial method. This experiment used 96 quail (Cortunix cortunix japonica), which were randomized into 6 treatments with 4 replications. Quails were divided into 6 groups and treated with different concentrations of turmeric flour and fish oil in each feed formula. The effects of different formula feeds were observed on changes in egg production and organoleptic changes. Egg production data were taken every day from week 3 to week 4 during the treatment period. The data taken is called Quail Day Production (QDP%). The organoleptic data of eggs were taken at the 3rd week of treatment and the preference test was carried out by 40 panelists on the aroma, taste and level of preference of quail eggs after being boiled. The addition of 0.3% turmeric flour significantly affected egg production but its combination with fish oil did not affect egg production. The combination of the concentration of turmeric flour and fish oil does not change the aroma of the eggs, but changes the taste of the eggs.